Indonesia : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
Staff Report for the 2012 Article IV consultation, prepared by a staff team of the IMF, following discussions that ended on July 6, 2012, with the officials of Indonesia on economic developments and policies. Based on information available at the time of these discussions, the staff report was completed on August 21, 2012. The views expressed in the staff report are those of the staff team and do not necessarily reflect the views of the Executive Board of the IMF.